2017
DOI: 10.1007/s11606-017-3997-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intrinsic Motivating Factors and Markers of Physician Well-Being: A National Physician Survey

Abstract: BACKGROUND: Although intrinsic motivating factors play important roles in physician well-being and productivity, most studies have focused on extrinsic motivating factors such as salary and work environment. OBJECTIVE: To examine the association of intrinsic motivators with physicians' career satisfaction, life satisfaction, and clinical commitment, while accounting for established extrinsic motivators as well. DESIGN AND PARTICIPANTS: A nationally representative survey of 2000 US physicians, fielded October t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 51 publications
4
85
1
Order By: Relevance
“…Consistent with previous studies 12,36 , male dentists appeared to have more work stress than female dentists in the vocational areas of the stress scale (P = 0.0338). Given that previous studies reported that intrinsic factors, such as vocational calling, are more closely related to the happiness or burnout of physicians than extrinsic factors, such as income 37,38 , the results of this study suggest that male dentists are more likely to be exposed to occupational stress in terms of intrinsic factors and, therefore, burnout. Further studies on the effects of sex on the dentist's job stress are warranted.…”
Section: Dentists' Job-related Stress According To Sociodemographic Amentioning
confidence: 51%
See 1 more Smart Citation
“…Consistent with previous studies 12,36 , male dentists appeared to have more work stress than female dentists in the vocational areas of the stress scale (P = 0.0338). Given that previous studies reported that intrinsic factors, such as vocational calling, are more closely related to the happiness or burnout of physicians than extrinsic factors, such as income 37,38 , the results of this study suggest that male dentists are more likely to be exposed to occupational stress in terms of intrinsic factors and, therefore, burnout. Further studies on the effects of sex on the dentist's job stress are warranted.…”
Section: Dentists' Job-related Stress According To Sociodemographic Amentioning
confidence: 51%
“…reported that the more physicians experienced burnout, the less likely they would find their work rewarding and the less intrinsic they would perceive their calling to medicine. Tak et al . also suggested that intrinsic motivators such as a calling, rather than an extrinsic motivator such as income, are associated with the physician's well‐being, including satisfaction, meaning and commitment.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, more attention has been focused on the importance of physician well-being. In this issue of JGIM, Tak et al 5 report on a survey of 2000 US physicians that examined the association of intrinsic motivators with career and life satisfaction as well as clinical commitment. As the authors point out, to date, most studies of physician well-being have Published online May 3, 2017 focused on extrinsic motivators (e.g.…”
mentioning
confidence: 99%
“…Motivation receives more and more attention in medical education research, albeit focusing predominantly on personal and social aspects of motivation. Intrapersonal aspects, for example, students’ motivational profiles or physicians’ intrinsic motives, such as having medicine as a calling and perceiving medicine as personally rewarding work, were important for learning, performance, well‐being or commitment . Studies on interpersonal aspects show that a sense of freedom or control over time and work, opportunities to learn and practice, constructive feedback, good collaboration and interaction with colleagues or supervisors, and a good educational climate may support motivation.…”
Section: Introductionmentioning
confidence: 99%